Prevalence of mandibular accessory foramina using CBCT in a selected iranian population - Nazmehr Vahdani; Fatemeh Ghobadi; Ali Bijani; Sina Haghanifar (Babol University of Medical Sciences, 2019)
Introduction: The aim of the current study was to evaluate the frequency of accessory foramina in human mandible. Materials & Methods: In this cross-sectional study, 400 cone-beam computed tomography (CBCT) scan images of mandibles of 273 patients (120 males and 153 females), divided into four groups ≤30, 30-39, 40-49, and ≥50 years) with the mean age of 38.05±13.71 years (40.71±12.83 for males and 35.39±12.05 for females) were evaluated. The number and diameter of accessory foramina from midline to anterior border of ramus with 0.1 mm intervals were investigated.Data were analyzed with SPSS 17 (SPSS Inc., Chicago, I1, USA) using T-Test, Pearson's correlation coefficient and Fisher exact test. Results: Totally, 568 accessory foramina with mean diameter of 0.35 ± 0.15 mm were seen. The frequency  of accessory foramina in the studied patients  was 83%  with mean frequency of 88% in males and 80% in females. These results showed a significant difference between the genders in frequency of accessory foramen (P<0.001) although no difference was observed among different age groups. The highest frequency belonged to anterior lingual of mandible. The frequency  of accessory foramina in posterior mandible was higher in females, while males indicated higher frequency in anterior mandible. No significant difference was found in the frequency of accessory foramina between the right and left sides of the mandible. Conclusion: The results suggested,the survey of accessory foramina is recommended in CBCT images of mandible for therapeutic reasons due to higher frequency of accessory foramina in mandible.